2015
DOI: 10.1017/s1368980015001718
|View full text |Cite
|
Sign up to set email alerts
|

Sodium content on processed foods for snacks

Abstract: Objective: To assess the Na content reported on the labels of processed foods sold in Brazil that are usually consumed as snacks by children and adolescents. Design: Cross-sectional study that assessed Na content and serving size reporting on processed food labels. Setting: A supermarket that is part of a large chain in Brazil. Subjects: All foods available for sale at the study's location and reported in the literature as snacks present in the diets of Brazilian children and adolescents. Results: Of the 2945 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…This result is in line with the findings of Kraemer et al 42 , who analyzed 2,945 processed foods sold in Brazil and found that 13.0% did not comply with the recommended serving sizes. This study also found similar percentages of products reporting serving sizes smaller (9.5%) and larger (4.3%) than those recommended by law.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in line with the findings of Kraemer et al 42 , who analyzed 2,945 processed foods sold in Brazil and found that 13.0% did not comply with the recommended serving sizes. This study also found similar percentages of products reporting serving sizes smaller (9.5%) and larger (4.3%) than those recommended by law.…”
Section: Discussionsupporting
confidence: 92%
“…Since Brazilians tend to consume these products in amounts larger than the serving sizes declared on their food labels and since trans fat content is not clearly and visibly shown on the food labels, consumers may be underestimating their trans fat consumption 41 . In addition a research study found great variability in the serving sizes and sodium content reported on the labels of processed snack foods (n=2,945) sold in Brazil 42 . Therefore, the acceptable range of 60% established by law seems to be excessive and may be leading to great variability in the serving sizes and nutritional information declared on labels and potentially to unhealthy food choices.…”
Section: Discussionmentioning
confidence: 99%
“…al. 15 in their study on processed foods for snacks marketed for children and adolescents in Brazil. The authors described that 14% of all the processed foods assessed did not comply the current serving size rule that makes the customers have difficulty to compare the Na content of similar foods.…”
Section: Methodsmentioning
confidence: 99%
“…4 However, the contribution of processed and ultraprocessed foods in children is also referred as a factor that may decrease the quality of diet in children considering that many foods exhibit unhealthy nutrient profiles, with higher amounts of sugar, trans fat, and sodium, compared with unprocessed or minimally processed foods; furthermore, after adjustment for energy intake, they may provide lower amounts of zinc, calcium, and vitamins A, B12, C, and E. 11 In infants and young children from Canada, 63% of the food products sold in Canada were reported as having high levels of sodium or sugar contribution to energy content, 12 and in Brazil, the analysis of 2945 processed foods that are usually consumed as snacks by children showed that 21% presented high levels of sodium. 13 Maalouf et al 14 assessed the sodium, sugar, and fat content of complementary infant and toddler foods sold in USA, and most commercial toddler meals, cereal bars and breakfast pastries, and infant-toddler snacks and desserts have high sodium contents or contain added sugars, suggesting a need for continued public health efforts to support families implementing healthy eating strategies.…”
mentioning
confidence: 99%